2014
DOI: 10.1002/app.40678
|View full text |Cite
|
Sign up to set email alerts
|

Melamine formaldehyde/polyvinyl alcohol composite fiber: Structure and properties manipulated by hydroxymethylation degree

Abstract: Composite fibers made of different hydroxymethylation degree (HMD) melamine formaldehyde (MF) resins and polyvinyl alcohol were prepared by wet spinning. The structures of MF resins and composite fibers were studied using Fourier transform infrared spectrometer, optical microscope, scanning electron microscope, differential scanning calorimetry, X-ray diffraction, and Kjeldahl. The fibers' mechanical properties, fire retardant properties, softening point in hot water, and thermal stability were also tested. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…While the coagulation bath used in the wet spinning process is not easy to handle but easily causes environmental pollution. [8][9][10] Electrospinning has become a popular spinning method in recent years. Acik et al 11,12 synthesized a quaternary ammonium salt functionalized polypropylene fiber by electrospinning, and then assembled layer-by-layer to obtain a mixed fiber mat composed of chlorinated polypropylene and chitosan fibers.…”
Section: Introductionmentioning
confidence: 99%
“…While the coagulation bath used in the wet spinning process is not easy to handle but easily causes environmental pollution. [8][9][10] Electrospinning has become a popular spinning method in recent years. Acik et al 11,12 synthesized a quaternary ammonium salt functionalized polypropylene fiber by electrospinning, and then assembled layer-by-layer to obtain a mixed fiber mat composed of chlorinated polypropylene and chitosan fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Wet spinning is the most common method to prepare MF fiber. But in wet spinning, MF prepolymer will be dissolved in the coagulation bath, and the main raw material of spinning solution will be wasted 9,14–16 . MF/PVA microfiber nonwoven fabric has been prepared by electrostatic spinning.…”
Section: Introductionmentioning
confidence: 99%
“…1,6 Moreover, considering the multihydroxyls of PVA and the water solubility of PVA and MF prepolymer, PVA is usually used as a toughening agent for MF resin. 7 -9 However, the low compatibility between MF resin and PVA at room temperature will always result in phase separation, thereby reducing the mechanical properties of the prepared material. 10 Therefore, the MF/PVA composite fiber must be produced as soon as the MF prepolymer/PVA blend is prepared; 11 to increase its toughness (the elongation at break > 30%), relatively large volumes (50 wt%) of PVA must be used as raw materials.…”
Section: Introductionmentioning
confidence: 99%
“…10 Therefore, the MF/PVA composite fiber must be produced as soon as the MF prepolymer/PVA blend is prepared; 11 to increase its toughness (the elongation at break > 30%), relatively large volumes (50 wt%) of PVA must be used as raw materials. 9 Yu et al investigated the effect of the multiphase structure of the MF/PVA blend system on the properties of MF/PVA composite fiber. 8 Xu et al reported that the MF resins with different hydroxymethylation degree have different compatibilities with PVA, and MF/PVA composite fibers were prepared by wetting spinning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation